Cytoplasmic collagen XIαI as a prognostic biomarker in esophageal squamous cell carcinoma. Issue 5 (4th May 2018) - Zhang, Bohan; Zhang, Cheng; Yang, Xuetao; Chen, Yue; Zhang, Hongqi; Liu, Jingshu; Wu, Qingchen
ABSTRACT: Stromal/cytoplasmic collagen XIαI (COL11A1) has been highlighted in the process of neoplastic transformation, including epithelial mesenchymal transition (EMT), metastasis and invasiveness. In this study, we aim to illuminate the clinical significance and biological role of COL11A1 in esophageal squamous cell carcinoma (ESCC). Herein, we investigated COL11A1 expression in 16 pairs of ESCC and adjacent normal tissues by RT-PCR and western blotting analysis. Correlations of COL11A1 expression with clinicopathologic parameters and survival status were then determined by immunohistochemistry in 116 ESCC and 50 normal specimens. Furthermore, bioinformatics was used for mechanisms exploration. And in vitro knockdown experiments were also performed. We found that COL11A1 expression was significantly higher in ESCC than in paired normal tissues at both mRNA and protein level. Immunohistochemistry showed that COL11A1 was predominantly localized to the cytoplasm rather than tumor stroma, patients with high COL11A1 expression had a poorer overall survival (OS) rate than those with low COL11A1 expression. Besides, increased COL11A1 expression was dramatically correlated with advanced clinical stage, invasion depth and lymph node metastases and served as an independent prognostic marker for ESCC. Likewise, COL11A1 dependent nomogram predicted a more precise survival outcome than traditional staging system. Moreover, COL11A1 silencing resulted in impaired cell proliferation and EMT, and subdued EMT inhibited cells aggressiveness. These biological processes (BPs) might be modulated by COL11A1 via the intracellular AKT/ERK/c-Myc cascades.